2015
DOI: 10.1093/hmg/ddv479
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale probabilistic 3D organization of human chromosome territories

Abstract: There is growing evidence that chromosome territories (CT) have a probabilistic non-random arrangement within the cell nucleus of mammalian cells including radial positioning and preferred patterns of interchromosomal interactions that are cell-type specific. While it is generally assumed that the three-dimensional (3D) arrangement of genes within the CT is linked to genomic regulation, the degree of non-random organization of individual CT remains unclear. As a first step to elucidating the global 3D organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 80 publications
1
26
0
Order By: Relevance
“…Thus, when measured at large genomic separations, each CT displays a different profile of genomic to spatial distances that are nonrandom. An exception was CT 17 whose MSD/FR plots were similar to its random simulations with only a small portion displaying nonrandom folding …”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, when measured at large genomic separations, each CT displays a different profile of genomic to spatial distances that are nonrandom. An exception was CT 17 whose MSD/FR plots were similar to its random simulations with only a small portion displaying nonrandom folding …”
Section: Introductionmentioning
confidence: 91%
“…The average distance between labeled DNA probes ranged from ~15 to 60 Mbp. At these large Mbp distances between probes, MSD analysis along with studies of the folding ratios (FRs) across the CT demonstrated that each CT had a specific folding pattern with some limited alterations across the cell cycle . Random simulation plots of all the CT except CT 17 were very different from the actual CT determinations and uniformly showed little or no changes in MSD or FRs across the entire simulated CT.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Physiological control of gene expression is dependent on chromatin context and requires timely and dynamic interactions between transcription factors and coregulatory machinery that reside in specialized subnuclear microenvironments . Multiple levels of nuclear organization functionally contribute to biological control and are perturbed in cancer . Morphologically, cancer nuclei are generally larger, more irregularly shaped, and have altered subnuclear structures .…”
Section: Introductionmentioning
confidence: 99%
“…These technological advances have enabled today's researchers to add detail to Boveri's concept. We have learned that chromosome territories are the structure of chromosomes in interphase nuclei (Cremer & Cremer, ; Cremer et al, ; Fritz et al, ; Sehgal et al, ) and were able to depict all of them together using successive hybridizations (Bolzer et al, ). We learned that chromosome positions are conserved during evolution (Tanabe et al, ) and that gene‐poor and gene‐dense chromosomes have their specific nuclear location in human cells (Tanabe et al, ).…”
Section: Introductionmentioning
confidence: 99%